2021
DOI: 10.3389/fmicb.2021.650513
|View full text |Cite
|
Sign up to set email alerts
|

Multigene Phylogeny and Morphology Reveal Three Novel Species and a Novel Record of Agaricus From Northern Thailand

Abstract: Agaricus is a saprophytic mushroom genus widely distributed throughout the world. In this study, a survey of the Agaricus species carried out around Chiang Mai University in northern Thailand from 2018 to 2019 yielded 12 collections. Morphological characteristics and phylogenic analyses based on the internal transcribed spacers (ITS) and a fragment of the large subunit (LSU) of the nuclear ribosomal DNA (rDNA), and a fragment of the translation elongation factor 1-alpha (tef1) genes were investigated. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Many studies have proposed that Thailand has proven to be a hot spot for novel species discovery [22]. Recently, this has been further evidenced by the discovery of many new species of macrofungi [23][24][25]. In this study, we found seven Volvariella specimens during our investigations of macrofungi in northern Thailand during the period from 2018 to 2020.…”
Section: Introductionmentioning
confidence: 60%
“…Many studies have proposed that Thailand has proven to be a hot spot for novel species discovery [22]. Recently, this has been further evidenced by the discovery of many new species of macrofungi [23][24][25]. In this study, we found seven Volvariella specimens during our investigations of macrofungi in northern Thailand during the period from 2018 to 2020.…”
Section: Introductionmentioning
confidence: 60%
“…The genus Agaricus L. (1753:1171) includes more than 600 species, according to the Catalogue of Life (Bánki et al 2023). Species of Agaricus are distributed throughout the world, except in Antarctica (Jaichaliaw et al 2021). Zhao et al (2016) proposed the segregation of this genus into five subgenera and 20 sections, considering the evolutionary divergence time as a standard taxonomic criterion.…”
Section: Introductionmentioning
confidence: 99%
“…Xanthodermatei and A. sect. Hondenses exhibit toxicity, such as A. xanthodermus Genev., which can induce gastrointestinal symptoms [49][50][51]. Despite a lack of research, A. daqinggouensis is unsuitable for consumption due to potential toxicity.…”
mentioning
confidence: 99%